Peran Pembelajaran Penjas Berbasis Life Skill terhadap Positive Youth Development dan Hasil Belajar: Systematic Literature Review - Firda Aulia; Yudy Hendrayana; Sucipto Sucipto (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aims to systematically review the literature related to the contribution of life skills-based physical education (PE) learning and learning outcomes to positive youth development (PYD). The method used in this study uses the SLR (Systematic Literature Review) method, literature searches are carried out using digital databases (Google Scholar, Publish or Perish, Scopus and others). The results of the analysis show that the PE learning model integrated with life skills has a positive impact on social competence, emotional regulation, and increased self-confidence of students. In addition, the achievement of learning outcomes in the cognitive, affective and psychomotor domains also supports the achievement of key indicators in the PYD framework, such as competence, confidence, character, connection and caring (5Cs). This study recommends the systematic integration of life skills-based pedagogical approaches in the PE curriculum to facilitate learners' holistic development.